Friday

April 18, 2014

April 18, 2014

Posted by **Lucas** on Sunday, February 3, 2013 at 12:05pm.

- Maths and science -
**Reiny**, Sunday, February 3, 2013 at 12:31pmterm(1) = 4 - 4(1/2)^1 = 4 - 2 = 2

term(2) = 4 - 4(1/2)^2= 4-4(1/4) = 3

term(3) = 4-4(1/2)^3

= 4 - 4(1/8)

= 4 - 4/8

= 4 - 1/2 = 3 1/2 or 7/2 or 3.5

so to get any term, e.g. term(5), replace n with the term number you want, in this case n=5

**Related Questions**

maths - the sum of the 4th and 6th terms of an A.P is 42. the sum of the 3rd and...

Further mathematics - An exponential sequence (GP)of positive terms and a linear...

Further mathematics - An exponential sequence of positive terms and a linear ...

maths - 1) The first term of arithmetic progression is -20 and the sum of it's ...

algebra 2 - An arithmetic progression has 5 terms that have a sum of 200. The ...

Math - Sum of4th and the 6th terms of an a,p is 42 . While the sum of the 3rd ...

Geometric - 1) The sum of last three terms of GP having n terms is 1024 time the...

maths - For an A.P. sum of 2n terms = 3* sum of n terms then sum of 3n terms : ...

maths - For an A.P. sum of 2n terms = 3* sum of n terms then sum of 3n terms : ...

Maths - Gemometric Progression - The sum of the first n terms of a series in n^3...